2018
DOI: 10.1590/0034-7167-2016-0623
|View full text |Cite
|
Sign up to set email alerts
|

Social determinants of health related to adhesion to mammography screening

Abstract: Objective: To identify proximal, intermediary and individual social determinants related to mammography adherence, according to the Social Determinants of Health model proposed by Dahlgren and Whitehead. Method: Correlational cross-sectional study, carried out with a sociodemographic and clinical data questionnaire and the Champion's Health Belief Model Scale, translated and adapted for use in Brazil. Data analyzed by multiple linear regression, from the domains scale, and sociodemographic and clinical variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 11 publications
1
8
0
3
Order By: Relevance
“…A Korean study found that living in a rural area was positively associated to have ever had a mammogram in women aged 40 to 74 years (Park et al, 2011). However, researchers from Argentina (PAHO, 2010), Brazil (Moreira et al, 2018), Mexico (Agudelo-Botero et al, 2013 and the US (Chandak et al, 2018) have reported a higher mammography uptake among residents of urban areas. Similar patterns have been found in eastern countries (Aminisani et al, 2016;Kulkarni et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Korean study found that living in a rural area was positively associated to have ever had a mammogram in women aged 40 to 74 years (Park et al, 2011). However, researchers from Argentina (PAHO, 2010), Brazil (Moreira et al, 2018), Mexico (Agudelo-Botero et al, 2013 and the US (Chandak et al, 2018) have reported a higher mammography uptake among residents of urban areas. Similar patterns have been found in eastern countries (Aminisani et al, 2016;Kulkarni et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Those covered by EsSalud and Private/Police and Armed forces were more than four times more likely to report MS. In Latin America, studies shows that women without health insurance are less likely to access MS than those who have insurance (Agudelo-Botero et al, 2013;Castillo-Ávila et al, 2014;Charry et al, 2008;Moreira et al, 2018;PAHO, 2010). Along with the lack of health insurance, the main barriers to accessing health care are financial problems, and poor health literacy (Mezones-Holguin et al, 2019;Soto, 2019), and these gaps are much wider if we look for vulnerable populations, whether in Peru (DGE, 2012) or other countries (Olorunsaiye et al, 2020;Olukotun et al, 2019;Steiness et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Women between the ages of 45 to 54 years have a higher risk of having a stroke than men in the same age group (4) . Another aspect to be considered in this group involves social and economic characteristicsunequal living and working conditions, culminating in different types of exposures and vulnerabilities (5) .…”
Section: Introductionmentioning
confidence: 99%
“…Various Brazilian studies have investigated mammography adherence (Moreira et al, 2018); however, there has been no knowledge synthesis that identifies the factors related to adherence across studies. An overall understanding of the factors that influence Brazilian women's use of mammography is foundational to identifying gaps in the literature, so as to inform future research endeavours as well as the development of effective health services that can create the conditions that promote adherence.…”
mentioning
confidence: 99%